Rice industry in Malaysia: challenges, policies and implications - Rajamoorthy, Yogambigai; Abdul Rahim, Khalid; Munusamy, Subramaniam (Elsevier, 2015)
Rice is the second most important crop in the world after wheat, with Asia being the largest producer and consumer. The National Agrofood Policy of Malaysia, 2011-2012 (Dasar Agromakanan Negara, DAN) had highlighted that local rice production should be increased to ensure the country'sdemand in future. However, to what extend this ensures food security in Malaysia was not supported empirically so far. The objective of this study is to estimate the future need of rice industry in Malaysia based on past performances. Using polynomial curve on historical production, consumption, export and import values from 1963 to 2013, this study has projected the production and consumption value for the 19-year period between 2012 and 2030. The results had revealed an increasing demand for rice with declining supply can be only off-set by import of rice in future.